Community Engagement Mechanisms : Field Experiment in Pakistan - Asim, Salman; Abbas, Ali; Adil, Mariam (World Bank, Washington, DC, 2015)
The overall objective was to elicit and sustain meaningful participation by the community in the management of schools. This could only be possible if the interface was integrated with local institutions. For this reason, School Management Committees in approximately half of the sample villages were strengthened through elections and capacity-building support to enable Committee members to effectively respond to community-identified needs. The primary purpose of this report is to record the rationale and motivations behind the decisions taken by the project team during the project’s design and implementation, and to catalyze a candid discussion about the challenges faced during implementation. The report is divided into three sections. The first section deals with the design phase of the project. There are two chapters in this section. The first lays out the framework and context for project design; the second discusses the design and testing of instruments, the portal, manuals and training of field facilitators. Section Two focuses on the implementation phase of the project. The first chapter in this section reviews village mobilization efforts and the convening of village-level meetings. The second chapter documents the post-meeting engagement process through the Community Dialogue Platform, while the third chapter reviews capacity-building support for newly constituted School Management Committees. The third and the final section reports the key findings from collation, synthesis and analysis of the process data collected for all interventions in this project. The first chapter in this section reports statistics on measures of participation and other indicators to measure treatment fidelity, strategies that measure accuracy and consistency of interventions. The second chapter analyzes text messaging traffic generated on the portal for the duration of the campaign, while the final chapter gives detailed expenditures analysis of School Improvement Plans developed by the School Management Committees.